2013
DOI: 10.1074/jbc.m112.444802
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C18:1-Phytoceramide as the Candidate Lipid Mediator for Hydroxyurea Resistance in Yeast

Abstract: Background: Deletion of the sphingolipid enzyme Isc1 in yeast makes cells sensitive to hydroxyurea. Results: Phytoceramides are the main sphingolipid involved in yeast cell response to hydroxyurea toxicity. Conclusion: C 18:1 -phytoceramides are identified as the specific ceramide that provide protection from hydroxyurea in a Cdc55-dependent manner. Significance: This is the first specific sphingolipid species identified to play a role in the genotoxic response pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 35 publications
3
37
0
Order By: Relevance
“…inactivation of Swe1 are dependent on sphingolipids. This is also consistent with a previous study that showed that the PP2A Cdc55 -Swe1 cascade is a downstream target of the sphingolipid, phytoceramide (59). We conclude that deletion of the regulatory subunit of PP2A Cdc55 makes the cells unresponsive to the availability of sphingolipids (SLs), which results in pertained activation of Swe1 and extension of the G1/S phase.…”
Section: Lipolysis-defective Mutants Accumulate Saturated and Unsatursupporting
confidence: 80%
“…inactivation of Swe1 are dependent on sphingolipids. This is also consistent with a previous study that showed that the PP2A Cdc55 -Swe1 cascade is a downstream target of the sphingolipid, phytoceramide (59). We conclude that deletion of the regulatory subunit of PP2A Cdc55 makes the cells unresponsive to the availability of sphingolipids (SLs), which results in pertained activation of Swe1 and extension of the G1/S phase.…”
Section: Lipolysis-defective Mutants Accumulate Saturated and Unsatursupporting
confidence: 80%
“…Similarly HU sensitivity of the csg2 Δ strain (Liu et al, 2011) was classified as cell-cycle related, and csg2 Δ also showed defective arrest of G1 phase under the stress of linoleic acid and hydroperoxide treatment (Fong et al, 2008). A more recent study (Matmati et al, 2013) showed sur4 Δ, double lag1 Δ, lac1 Δ made cells more sensitive to HU. Moreover, depletion of phytoceramide by overexpressing YPC1 rendered wild type cells sensitive to HU.…”
Section: Phenotypes Of the Yeast Sphingolipid Pathwaymentioning
confidence: 96%
“…In addition, loss of Δψ m decreases TORC1-mediated Sch9p phosphorylation [87]. Despite the fact that the retrograde response is not activated in Δisc1 mutants [28], several cellular responses during the retrograde response are also observed in Δisc1 mutants [18, 20, 44, 92, 94-96, 98]. This indicates that loss of mitochondrial quality, which triggers the retrograde response, interacts with SL homeostasis, and SL signaling activates pathways in Δisc1 mutants that resemble responses to retrograde signaling.…”
Section: Discussionmentioning
confidence: 99%
“…3). For instance, while Rtg2p or Rtg3p upregulate expression of SWE1 [92], encoding the Swe1p protein kinase involved in G2/M transition [93], phytoCer generated by Isc1p regulates Swe1p levels [18, 94]. Additionally, the protein product of RSB1 , whose expression of the encoding gene increases in a Pdr3p-dependent manner upon loss of the mitochondrial genome [44, 95, 96], removes LCBs from the cell [97] and is also increased in Δisc1 mutants [20].…”
Section: The Retrograde Response Interacts With Sphingolipid Homeomentioning
confidence: 99%